L’ANALYSE DES CAUSES MAJEURS DE LA NON PERFORMANCE DES FINANCES PUBLIQUES EN REPUBLIQUE DEMOCRATIQUE DU CONGO - lupapa, moses kalombo; Ndala Clovis, Masumbuko (IJRDO - Journal of Business Management, 2023)
In the DRC, the execution of revenue and expenditure is characterized by the consumption of revenue often at source by the services responsible for their collection, fraud fostered by corruption, influence peddling and impunity is increasing more and more, tax and customs exemptions are to be mentioned, non-compliance with budget appropriations some credits are executed in excess, Others do not even know a start of execution, the execution of unforeseen expenditure (100-day project), the violation of the rules relating to the procedure for the execution of public expenditure by the use of exceptional procedures, the violation of public procurement rules, to name but a few. Faced with this, Law No. 18/010 of 9 July 2018 amending Law No. 11/011 of 13 July 2011 on public finances in the Democratic Republic of Congo advocates in its explanatory memorandum a budget based on a logic of results through program budgets. The law aims to move from a budget of means to that of a budget of results. This is a performance-oriented management approach, that is, the search for economic effectiveness and efficiency in the use of resources and the achievement of objectives previously defined in the programs. In view of the above, a question deserves to be asked in this research, what are the major causes of the non-performance of public finances in the Democratic Republic of Congo?